Innate immunity: regulation of caspases by IAP‐dependent ubiquitylation - Falschlehner, Christina; Boutros, Michael (The EMBO journal, 2012)
Caspases are widely known as initiators and executioners of cell death. Full activation of caspases leading to cleavage of many cellular substrates was long considered to be a point‐of‐no‐return in the apoptosis pathway. However, it also has been known that activated caspases do not always have the ability to kill, but instead initiate non‐apoptotic processes such as cell differentiation or activation of innate immune responses. In this issue of The EMBO Journal, Meinander et al (2012) explore the contribution of polyubiquitination of Dredd, a known initiator caspase, to the activation of innate immunity. The authors show that infection with gram‐negative bacteria leads to DIAP2‐dependent ubiquitylation of Dredd which in turn is required for processing of Relish (Rel) and expression of antimicrobial peptide (AMP) genes that are indispensable for fighting the infection.